Fractionation of Heavy Metals in Multi-Contaminated Soil Treated with Biochar Using the Sequential Extraction Procedure - Awad, Mahrous; Liu, Zhongzhen; Skalicky, Milan; Dessoky, Eldessoky S; Brestic, Marian; Mbarki, Sonia; Rastogi, Anshu; El Sabagh, Ayman (Biomolecules, 2021)
Heavy metals (HMs) toxicity represents a global problem depending on the soil environment's geochemical forms. Biochar addition safely reduces HMs mobile forms, thus, reducing their toxicity to plants. While several studies have shown that biochar could significantly stabilize HMs in contaminated soils, the study of the relationship of soil properties to potential mechanisms still needs further clarification; hence the importance of assessing a naturally contaminated soil amended, in this case with Paulownia biochar (PB) and Bamboo biochar (BB) to fractionate Pb, Cd, Zn, and Cu using short sequential fractionation plans. The relationship of soil pH and organic matter and its effect on the redistribution of these metals were estimated. The results indicated that the acid-soluble metals decreased while the fraction bound to organic matter increased compared to untreated pots. The increase in the organic matter metal-bound was mostly at the expense of the decrease in the acid extractable and Fe/Mn bound ones. The highest application of PB increased the organically bound fraction of Pb, Cd, Zn, and Cu (62, 61, 34, and 61%, respectively), while the BB increased them (61, 49, 42, and 22%, respectively) over the control. Meanwhile, Fe/Mn oxides bound represents the large portion associated with zinc and copper. Concerning soil organic matter (SOM) and soil pH, as potential tools to reduce the risk of the target metals, a significant positive correlation was observed with acid-soluble extractable metal, while a negative correlation was obtained with organic matter-bound metal. The principal component analysis (PCA) shows that the total variance represents 89.7% for the TCPL-extractable and HMs forms and their relation to pH and SOM, which confirms the positive effect of the pH and SOM under PB and BB treatments on reducing the risk of the studied metals. The mobility and bioavailability of these metals and their geochemical forms widely varied according to pH, soil organic matter, biochar types, and application rates. As an environmentally friendly and economical material, biochar emphasizes its importance as a tool that makes the soil more suitable for safe cultivation in the short term and its long-term sustainability. This study proves that it reduces the mobility of HMs, their environmental risks and contributes to food safety. It also confirms that performing more controlled experiments, such as a pot, is a disciplined and effective way to assess the suitability of different types of biochar as soil modifications to restore HMs contaminated soil via controlling the mobilization of these minerals.
Keywords: oxidy; mikroskopie elektronová rastrovací; Oxides; Zinc; Copper; dřevěné a živočišné uhlí; Hydrogen-Ion Concentration; organické látky; chemická frakcionace; Cadmium; biochar; olovo; půda; bamboo; kadmium; Charcoal; sloučeniny manganu; Soil; Principal Component Analysis; Microscopy, Electron, Scanning; spektrometrie rentgenová emisní; zinek; Lead; hluchavkotvaré; distribution; Metals, Heavy; analýza hlavních komponent; Sasa; těžké kovy; měď; železité sloučeniny; Ferric Compounds; paulownia; Organic Chemicals; koncentrace vodíkových iontů; znečištění životního prostředí; Spectrometry, X-Ray Emission; availability; Lamiales; Environmental Pollution; Chemical Fractionation; Manganese Compounds; heavy metals